Analysis of management factors influencing Anaplasma marginale transmission - Morel, Nicolas; Mastropaolo, Mariano; Torioni, Susana Marta; Signorini Porchiett, Marcelo Lisandro; Mangold, Atilio Jose; Primo, María Evangelina (Elsevier, 2024)
The aim of this study was to identify factors that play a key role in the epidemiology of bovine anaplasmosis by adapting a model primarily developed for cattle babesiosis. A cross-sectional observational study was conducted to study the proportion of calf herds in endemic stability/instability for A. marginale in a semi-arid area of Argentina. The A. marginale inoculation rate (h) was calculated from age-specific seroprevalence using double-antigen sandwich ELISA in 58 herds of 4.5–8.5-month–old calves. Herds were considered to be in endemic instability (EI) at h < 0.005 and, therefore, at risk of anaplasmosis outbreaks. A generalized linear model was performed to explore husbandry practices associated with differences in A. marginale transmission. Additionally, spatial clustering of herds with the same immunological status was analyzed using spatial scan statistics (SatScan, Bernoulli model). Spearman's correlation was used to explore a possible association between A. marginale h and Babesia bovis and B. bigemina h (data obtained in previous works). Almost half (43 %) of the herds were in the EI zone for A. marginale. Calves raised under forage combinations had a greater risk of being in EI (OR = 5.41, CI95 %OR = 1.43–20.41) than those reared exclusively on permanent pastures, where cattle density is higher (P = 0.01). Moreover, calves from herds treated only with pyrethroids to control ticks had more chances of being in EI (OR = 4.16, CI95 %OR = 1.12–15.38) than calves from herds receiving different acaricide combinations (P = 0.03). Calves from herds subjected to more than two treatments against Haematobia irritans had higher odds for EI (OR = 5.69, CI95 %OR = 1.24–26.11) than those from herds using fewer than two treatments (P = 0.02). The spatial analysis revealed no spatial clustering of the immune status of the herds (P = 0.67 and P = 0.74 for low and high incidence rates, respectively). A significant variation between farms was observed in A. marginale h (CV = 90.38 %). The correlation analysis revealed a strong epidemiological link of A. marginale h with B. bovis h (Rho=0.794, P<0.001) and B. bigemina h (Rho=0.839, P<0.001). Given that R. microplus is the only vector of B. bovis and B. bigemina in the region, the results of this work strongly suggest an active and significant role of R. microplus in the transmission of A. marginale.